Yearbook of the German Cognitive Linguistics Association (De Gruyter Mouton, 2013)
The Yearbook of the German Cognitive Linguistics Association documents the exchange of ideas in the Cognitive Linguistics research community and related fields, not just in Germany but all over the world. It brings together researchers from a variety of theoretical and methodological frameworks, whose work is informed by a broad view of language both as an integral part of human cognition and as a set of socially situated communicative practices.